Optimization-based freeform shape reconstruction - Liu, Yang (2013)
This paper proposes a novel method to reconstruct cylinder-like freeform shapes from the parallel projection of their contours. There are three main steps: 1) Transform the curved drawing into a straight line drawing by converting the curves into polylines using dynamic time warping. Triangular or quadrilateral faces are created by joining corresponding points on opposite curves. 2) Obtain the 3D coordinates of the vertices in the straight line drawing using an optimization-based method. 3) Recover the cross sections internal to the boundary and interpolate them to obtain the cylinder surface. Step 3 forms the main original contribution of this work. Our implementation of the method produces results that are consistent with human perception of the curved drawings as 3D shapes